Modele autoregresji z rozłożonymi opóźnieniami w benchmarkingu konkurencyjności regionów - Welc, Jacek (Autoregressive Distributed Lags Models in Benchmarking of Regions Competitiveness, 2006)
The article presents proposed methodology of dynamic analysis of changes in regions competitiveness. Autoregressive distributed lags models constitute the main tool of the presented procedure. They enable identification of factors determining the level of regions competitiveness. The methodology makes also possible the analysis of changes in time of the degree of competitiveness of individual regions. In conjunction with traditional multidimensional classification methods the proposed methodology enables the choice of the benchmark, i.e. the region of the highest potential of development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 267-276